A revision of Petasiger Dietz, 1909 (Digenea: Echinostomatidae) and a key to its species - Faltýnková, Anna; Gibson, David I; Kostadinova, Aneta (Systematic parasitology, 2008)
Petasiger Dietz, 1909 is revised, and a key to and lists of the records and hosts of the 18 recognised species are presented. The recognised species are: P. exaeretus Dietz, 1909, P. australis Johnston & Angel, 1941, P. combesi Zamparo, Overstreet & Brooks, 2005, P. floridus Premvati, 1968, P. grandivesicularis Ishii, 1935, P. islandicus Kostadinova & Skirnisson, 2007, P. johnstoni n. sp., P. megacanthus (Kotlán, 1922), P. minutissimus Gogate, 1934, P. neocomense Fuhrmann, 1927, P. nitidus Linton, 1928, P. novemdecim Lutz, 1928, P. oschmarini Kostadinova & Gibson, 1998, P. phalacrocoracis (Yamaguti, 1939), P. pseudoneocomense Bravo-Hollis, 1969, P. pungens (Linstow, 1894), P. soochowensis Ku, Chiu, Li & Zhu, 1977 and P. variospinosus (Odhner, 1910). Seven of these species are redescribed on the basis of type and newly collected material. P. laricola Ku, Chiu, Li & Zhu, 1977, Echinochasmus fotedari Chishti & Mir, 1989 and P. neocomense of Canković, Kazić & Milka (1983) are considered synonyms of P. pungens; P. longicirratus Ku, 1938, P. skrjabini Bashkirova, 1941 and P. nitidus of Chen et al. (1985) synonyms of P. neocomense; P. caribbensis Nassi, 1980 a synonym of P. novemdecim; and P. tientsinensis Ku, Chiu, Li & Zhu, 1977 a synonym of P. exaeretus. P. johnstoni n. sp. is described from Tachybaptus ruficollis novaehollandiae in Australia. It is readily distinguished from the most closely-related P. grandivesicularis Ishii, 1935 and P. australis Johnston & Angel, 1941 by the smaller size of the body and angle collar spines and differences in most other metrical characters. Species attributed to Petasiger which are here considered species inquirendae are: P. antigonus Nigam, 1944 sp. inq., P. chandleri Abdel-Malek, 1952 sp. inq., P. jubilarum Elperina in Skrjabin, Petrov & Bashkirova, 1947 sp. inq., P. nicolli Pande, 1939 sp. inq. and P. spasskyi Oshmarin in Skrjabin, Petrov & Bashkirova, 1947 sp. inq.; and Echinoparyphium inopinatum (Baer, 1959) n. comb. is a species previously attributed to Petasiger.
Keywords: Bird Diseases; nemoci ptáků; Echinostomatidae; infekce červy třídy Trematoda; ptáci; Birds; Animals; Trematode Infections; zvířata